The Cultural Left and the Reagan Era : U.S. Protest and Central American Revolution. - Witham, Nick (I.B. Tauris, 2015)
"The Reagan era is usually seen as an era of unheralded prosperity, and as a high-watermark of Republican success. President Ronald Reagan's belief in "Reaganomics", his media-friendly sound-bites and "can do" personality have come to define the era. However, this was also a time of domestic protest and unrest. Under Reagan the US was directly involved in the revolutions which were sweeping the Central Americas- El Salvador, Honduras and Guatemala -and in Nicaragua Reagan armed the Contras who fought the Sandinistas. This book seeks to show how the left within the US reacted and protested against these events. The Nation, Verso Books and the Guardian exploded in popularity, riding high on the back of popular anti-interventionist sentiment in America, while the film-maker Oliver Stone led a group of directors making films with a radical left-wing message. The author shows how the1980s in America were a formative cultural period for the anti-Reaganites as well as the Reaganites, and in doing so charts a new history."--Bloomsbury Publishing.